A new occurrence specie in Corchorus L. (Tiliaceae Juss.) for flora of Vietnam - Xuyen, Do Thi (Academia Journal of Biology, 2012)
According to C. Phengklai, the genus Corchorus L. had about 100 species in the world. There were 3 Corchorus species in Vietnam: Corchorus aestuans L., Corchorus capsularis L., Corchorus olitolaris L.. Some of them were used as vegetables and medicinal plants especially for good fibres from bark (Corchorus capsularis L., Corchorus olitolaris L.).... During the study of speciment and documents of Tiliaceae of Vietnam, we have found one new occurrence specie of Corchorus: C. siamensis Craib for the flora of Vietnam, which is recorded endemic to Thailand before. C. siamensis Craib is annual herb, up to 50 cm high. Leaves ovate 3-7 ´ 1.3-3.5 cm; apex cuspidate; base rounded or obtuse; at the base without a pair of filiform appendages. Inflorescence solitary or in pairs, opposite the leaf; flower buds oblong. Sepals lanceolate. Petal linear. Stamens glabrous. Ovary oblong, hairy. Fruit cylindrical, slightly narrow toward acuminate apex. Voucher specimens were collected on Truong Sa island in Khanh Hoa province and deposited in the Herbarium of the Institute of Ecology and biological Resources, Hanoi, Vietnam (HN)